Parental Anxiety and Parental Criticism as Predictors of Child Internalizing Symptoms - Okonkwo, Adaeze; Dlamini, Thandiwe (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the predictive roles of parental anxiety and parental criticism on child internalizing symptoms in a South African sample. Methods: The research employed a correlational descriptive design with a sample of 470 parents of children aged 6 to 12 years, selected based on the Morgan and Krejcie sample size table. Participants were recruited from various regions of South Africa. Standardized instruments were used, including the Child Behavior Checklist (CBCL) for child internalizing symptoms, the Beck Anxiety Inventory (BAI) for parental anxiety, and the Perceived Criticism Measure (PCM) for parental criticism. Data were analyzed using SPSS version 27, applying Pearson correlation coefficients to examine the relationships between variables and multiple linear regression to determine the predictive power of parental anxiety and criticism on child internalizing symptoms. Findings: Pearson correlation analysis showed significant positive relationships between child internalizing symptoms and both parental anxiety (r = .61, p < .01) and parental criticism (r = .53, p < .01). Multiple linear regression analysis revealed that both parental anxiety (β = .49, t = 12.67, p < .001) and parental criticism (β = .33, t = 8.82, p < .001) significantly predicted child internalizing symptoms. The overall model was statistically significant (F(2, 467) = 183.19, p < .001), with an R² of .44, indicating that 44% of the variance in child internalizing symptoms was explained by the two predictors. Conclusion: The findings demonstrate that higher levels of parental anxiety and criticism are associated with increased internalizing symptoms in children. These results highlight the importance of addressing both emotional and behavioral aspects of parenting in preventive and therapeutic interventions aimed at supporting child mental health.